The effects of single versus repeated plyometrics on landing biomechanics and jumping performance in men - Makaruk, H.; Czaplicki, A.; Sacewicz, T.; Sadowski, J. (Biology of Sport, 2014)
The aim of this study was to examine the chronic effects of single and repeated jumps training on vertical landing force (VGRF) and jump height in untrained men. The VGRF and jump height were compared after a six-week plyometric training programme containing single and repeated jumps, together with two additional parameters: landing time (LT) and range of the knee flexion during landing (KF). Thirty-six untrained physical education students with a plyometric training background were randomly assigned to a single jump group (SJG, n =12), repeated jumps group (RJG, n =12), and control group (CON, n =12). The SJG performed only single jumps, the RJG executed repeated (consecutive) jumps, whereas the CON did not perform any exercises at all. A countermovement jump (CMJ), repeated countermovement jumps (RCMJ), and a drop jump (DJ) were tested before and after the training. Only the RJG showed a significantly reduced VGRF (p<0.05) in all tests. Both plyometric groups significantly improved (p<0.05) their jump height in all tests. The LT was significantly greater in the RJG, compared to the SJG, in all tests. The KF was also significantly (p<0.05) greater in the RJG than in the SJG for CMJ and RCMJ. The results suggest that repeated jumps are beneficial for simultaneous landing force reduction and jumping performance enhancement.